2016
DOI: 10.3892/mco.2016.1066
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of serum lactate dehydrogenase levels in Ewing's sarcoma: A meta-analysis

Abstract: Abstract.A number of studies have investigated the role of serum lactate dehydrogenase (LDH) levels in patients with Ewing's sarcoma, although these have yielded inconsistent and inconclusive results. Therefore, the present study aimed to systematically review the published studies and conduct a meta-analysis to assess its prognostic value more precisely. Cohort studies assessing the prognostic role of LDH levels in patients with Ewing's sarcoma were included. A pooled hazard ratio (HR) with 95% confidence int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 32 publications
0
28
0
Order By: Relevance
“…The guidelines recommend measuring LDH level as a tumor marker since it usually correlates with tumor burden and has a prognostic value in ES/PNET [9,10]. Also, a meta-analysis indicated that patients with high serum levels of LDH have a poor prognosis compared to patients with normal serum LDH values [20]. Previous studies showed that tumor size of 8 cm or more is associated with poor survival [3,21].…”
Section: Discussionmentioning
confidence: 99%
“…The guidelines recommend measuring LDH level as a tumor marker since it usually correlates with tumor burden and has a prognostic value in ES/PNET [9,10]. Also, a meta-analysis indicated that patients with high serum levels of LDH have a poor prognosis compared to patients with normal serum LDH values [20]. Previous studies showed that tumor size of 8 cm or more is associated with poor survival [3,21].…”
Section: Discussionmentioning
confidence: 99%
“…An elevated serum lactate dehydrogenase (LDH) reflects tumor burden, and Li et al revealed in a meta-analysis that higher levels of LDH are associated with a poorer overall survival and disease-free survival at five years. 12 The classic radiographic appearance of Ewing's sarcoma typically involves a poorly defined, permeative, and destructive intramedullary lesion with onion-skin appearing periosteal elevation and an associated soft-tissue mass. 10 ►Fig.…”
Section: Ewing's Sarcomamentioning
confidence: 99%
“…As mentioned, human LDH-A has been found overexpressed in various cancer tissues, including sarcomas [137,138]. Genetic silencing of LDH-A caused a reduced OS cell proliferation and migration in vitro, and in impaired tumorigenesis in vivo [139].…”
Section: Lactate and Sarcomasmentioning
confidence: 86%